(untitled) (Ecological Bulletin of Kryvyi Rih District, 2023)
The development of minerals within the technogenically loaded regions leads to a decrease in areas and, accordingly, the habitats of wild plant species. Among wild plant species, special attention should be paid to species that reduce populations and need to preserve their numbers — protected species. Solving the problem of protected species conservation is carried out by compensating the state for the impact on plants associated with the extraction of minerals in the territory of their growing. This method does not solve the problem of preservation of species and phytodiversity as a whole. A promising direction is the reintroduction (resettlement) of species from natural habitats to loci located in used-up parts of quarries, industrial sites, etc. The reintroduction of the species Adonis vernalis L., Tulipa schrenkii Regel from natural habitats in the Severnaya ravine, which is located in the zone of expansion of the mining enterprise into the exhausted part of the Zhovtokamyansky open pit (Apostolivskyi district of the Dnipropetrovsk region), was carried out according to generally known approaches. The reintroduction took place in November 2020. In March 2021, populations of Adonis vernalis L. were in the generative phase and Tulipa schrenkii Regel in the virgin phase. Further research did not reveal the beginning of the flowering process in Schrenka’s tulip. The assessment of the effectiveness of the reintroduction of these protected species is preliminary. The possibility and necessity of taking measures to preserve phytodiversity in the conditions of mineral development without transferring plants to the territory of the nature reserve fund is shown. Plant reintroduction is becoming an increasingly used strategy for plant conservation, requiring improvement of modern methods, mapping of habitat suitability for endangered plant species. The importance of reintroduction as an element of the conservation paradigm of industrial botany is emphasized